Influence of the interventionist's experience on outcomes of endovascular thrombectomy in acute ischemic stroke: results from the MR CLEAN Registry. (20th January 2022) - Olthuis, Susanne G H; den Hartog, Sanne J; van Kuijk, Sander M J; Staals, Julie; Benali, Faysal; van der Leij, Christiaan; Beumer, Debbie; Lycklama à Nijeholt, Geert J; Uyttenboogaart, Maarten; Martens, Jasper M; van Doormaal, Pieter-Jan; Vos, Jan Albert; et al.
Abstract : Background: The relationship between the interventionist's experience and outcomes of endovascular thrombectomy (EVT) for acute ischemic stroke of the anterior circulation, is unclear. Objective: To assess the effect of the interventionist's level of experience on clinical, imaging, and workflow outcomes. Secondly, to determine which of the three experience definitions is most strongly associated with these outcome measures. Methods: We analysed data from 2700 patients, included in the MR CLEAN Registry. We defined interventionist's experience as the number of procedures performed in the year preceding the intervention (EXPfreq), total number of procedures performed (EXPno), and years of experience (EXPyears). Our outcomes were the baseline-adjusted National Institutes of Health Stroke Scale (NIHSS) score at 24–48 hours post-EVT, recanalization (extended Thrombolysis in Cerebral Infarction (eTICI) score ≥2B), and procedural duration. We used multilevel regression models with interventionists as random intercept. For EXPfreq and EXPno results were expressed per 10 procedures. Results: Increased EXPfreq was associated with lower 24–48 hour NIHSS scores (adjusted (a)β:−0.46, 95% CI −0.70 to −0.21). EXPno and EXPyears were not associated with short-term neurological outcomes. Increased EXPfreq and EXPno were both associated with recanalization (aOR=1.20, 95% CI 1.11 to 1.31 and aOR=1.08, 95% CI 1.04 to 1.12, respectively), and increased EXPfreq, EXPno, and EXPyears were all associated with shorter procedure times (aβ:−3.08, 95% CI−4.32 to −1.84; aβ:−1.34, 95% CI−1.84 to −0.85; and aβ:−0.79, 95% CI−1.45 to −0.13, respectively). Conclusions: Higher levels of interventionist's experience are associated with better outcomes after EVT, in particular when experience is defined as the number of patients treated in the preceding year. Every 20 procedures more per year is associated with approximately one NIHSS score point decrease, an increased probability for recanalization (aOR=1.44), and a 6-minute shorter procedure time.